الجزاء المترتب على الإخلال بالالتزام بالإعلام الالكتروني (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يعد الالتزام بالإعلام أحد التطبيقات العملية لمبدأ حسن النية الذي ينطوي على وجوب أن تسود الثقة والأمانة والصدق كافة مراحل العقد، وأحد الطرق التي يمكن من خلالها سد النقص الذي يعتري نظرية عيوب الإرادة، ونظراً إلى دوره المهم في خلق إرادة حرّة لدى المخاطب بمضمونه، وتبعاً لذلك كان لزاماً أن نبيّن الجزاء المترتب على الإخلال به، وخاصةً حينما يجد المتعاقد نفسه امام عقدٍ لا يلبي حاجاته. تتناول هذه الدراسة التعريف بمفهوم الالتزام بالإعلام الالكتروني المقرر لمصلحة المستهلك كونه الطرف الضعيف في العلاقة العقدية تبعاً للوسيلة المعتمدة في التعاقد، وهو أبرز الالتزامات التي يتعيّن على المهني أن يتحلّى بها في ابرام أي عقد عامّة، والعقد الالكتروني خاصةً حتّى يكون الدائن بالالتزام المذكور(المستهلك) على بيّنةٍ كاملةٍ من أمره إزاء ما يقدم عليه.   Commitment to information is one of the practical applications of the principle of good faith, which implies that trust, honesty must prevail throughout all stages of the contract, and one of the ways in which the deficiency of the theory of wills can be bridged and given its important role in creating a free will for the communicator. It was necessary to show the penalty resulting from the breach, especially when the contractor finds himself in front of a contract that does not meet his needs This study deals with the definition of the concept of commitment to information intended for the benefit of the consumer being the weak party in the contractual relationship according to the means adopted in the contract, which is the most important obligations that a professional must have in any general contract, and electronic contract in particular so that the creditor  in question is fully aware of His order